Violence against women - Ahuja, Ram (Rawat Publications, 1998)
"Atrocities against women are on the rise. What types of women are the victims of violence? What types of males are the perpetrators of crimes? Could any theoretical analysis be offered for explaining the etiology of violence by males against females? Will taking up the cudgel by women's organizations on behalf of the victims and women's self-awareness and using bold and courageous steps to face the physical and mental torture and sexual harassment prove effective? This book examines these aspects and some more crucial issues with a sociological perspective. It also assesses the issue as to how the victims of violence face the shock and attempt to adjust themselves in the social environment, in spite of the biased attitudes, lack of sympathy and callousness of the concerned agencies. A number of initiatives have also been proposed to tackle the most gruesome problem of violence against women.Providing a balance between practical and theoretical issues and concerns, the book is an essential reading for sociologists, criminologists, psychologists, women activists, health care workers and social workers."